2018
DOI: 10.4236/abb.2018.99030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Liver Cancer Prevention of Anthocyanin Extracts from Mulberry (<i>Morus alba</i> L.) Variety PR-01

Abstract: This study aims to evaluate the preventive effects of anthocyanins extracts (MAEs) from mulberry variety PR-01 against N-nitrosodiethylamine (NDEA)induced hepatocarcinogenesis in rats. It was found that 150 mg•kg −1 MAEs treatment significantly reduced the NDEA-induced hepatic nodules incidence and hepatocellular carcinoma incidence by 58.30% and 41.70% compared to the model group. Meanwhile, MAEs significantly restored the elevated the liver function enzymes, inhibited the tumor necrosis factor alpha and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…In this study, the hepatic GST and UGT concentrations in the NDEA group was remarkably ( p < 0.001) reduced as compared to the control group, which is consistent with earlier reports (Liao, Liu, Xu, & Zheng, ). Compared with the NDEA group, the hepatic tissue GST and UGT were significantly increased in the NDEA + CFT‐1 group by 63.94% and 57.95%, respectively (Figure c, p < 0.001).…”
Section: Resultssupporting
confidence: 93%
“…In this study, the hepatic GST and UGT concentrations in the NDEA group was remarkably ( p < 0.001) reduced as compared to the control group, which is consistent with earlier reports (Liao, Liu, Xu, & Zheng, ). Compared with the NDEA group, the hepatic tissue GST and UGT were significantly increased in the NDEA + CFT‐1 group by 63.94% and 57.95%, respectively (Figure c, p < 0.001).…”
Section: Resultssupporting
confidence: 93%
“…Liao et al, found that 150 mg•kg −1 anthocyanins extracted from mulberries reduce the incidence of liver cancer induced by N-nitrosodiethylamine by half. The protective effect of anthocyanin extract against liver cancer is related to a decrease in the expression of the inflammatory mediator COX-2, which, through the NF-κB pathway, induces the expression of antioxidant enzymes and reduces lipid peroxidation [106]. As nutritional supplements, anthocyanins from blueberries can suppress the development of hepatocellular carcinoma by inhibiting invasion, apoptosis, migration, and proliferationrelated pathways [107].…”
Section: Liver Cancermentioning
confidence: 99%
“…Also, anthocyanins have the potential of modulating signaling pathways that are deregulated in cancers (Kausar et al, 2012). There is evidence that anthocyanin-rich extracts from some plants (e.g., Ribes nigrum and Morus alba) have a chemopreventive effect against HCC induction in animal models (Bishayee et al, 2011;Liao, Liu, Xu, & Zheng, 2018).…”
Section: Introductionmentioning
confidence: 99%